Meningkatkan Hasil Kemampuan Belajar Pendidikan Agama Islam Menggunakan Metode Ceramah Kelas IV di SDN 14 Langung Sepakat - Ermailis, Ermailis (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
Islamic Religious Education (IRE) plays an important role in character formation, but it often faces challenges in terms of active student involvement and in-depth understanding of the material. One solution to address this issue is through the use of more innovative teaching methods. This study aims to determine whether the use of the lecture method can improve student learning outcomes in the IRE subject in the fourth grade of SDN 14 Langung Sepakat. The lecture method is expected to enhance student participation, motivation, and critical thinking skills. This study employs a quantitative approach with a classroom action research design. Data was collected through observations, tests, and interviews. The results of the study indicate a significant improvement in student learning outcomes after the implementation of the lecture method. This is expected to serve as a reference for the development of more effective teaching methods in Islamic Religious Education.